Innovating Reading Competency Assessment Tool Using the PISA Standard in Arabic Textbooks for 8th Graders - Iis Dahlia; R. Umi Baroroh; Zaffa Izzatul Islamiah; Bellah Asa O’Neal Elmi; Ahmad Zulkarnain; Luthfi Qolbi Azzahra; Muhammad Mahmud Abdulqadir Ali (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research was intended to apply PISA standards to the Arabic textbooks for 8th grade students published by the Ministry of Religious Affairs in 2020. Lliterature research was performed on the primary data sourced from Arabic textbooks and secondary data from relevant books and journal articles. The data then underwent content analysis and descriptive analysis through several steps: data collection, data filtering, and selection and qualitative data interpretation. The results showed that although the assessment instruments in the Arabic textbook for 8th grade in 2020 covered the aspects of PISA, most of the instruments were at lower levels, such as three instruments at level 1b, two instruments at level 2, three instruments at level 3, and one instrument at level 4. Based on the results of the analysis, instrument innovation was carried out with PISA standards at levels 4-6, consisting of five level 4 instruments, five level 5 instruments, and one level 6 instrument. These innovations included analysis and interpretation, critical evaluation and reflection, and high-level analysis and synthesis for better comprehension and function in Arabic reading competence assessment